A Soluble Form of P Selectin Glycoprotein Ligand 1 Requires Signaling by Nuclear Factor Erythroid 2–Related Factor 2 to Protect Liver Transplant Endothelial Cells Against Ischemia–Reperfusion Injury. Issue 6 (6th February 2017) - Zhang, C.; Zhang, Y.; Liu, Y.; Liu, Y.; Kageyama, S.; Shen, X.–d.; Gao, F.; Zheng, S.; Busuttil, R. W.; Shaw, G. D.; Ji, H.; Kupiec‐Weglinski, J. W.
Abstract : Liver endothelial cell (LEC) damage is essential in the pathogenesis of ischemia–reperfusion injury (IRI) in transplant recipients. We analyzed the mechanism of LEC resistance against IRI by using a novel recombinant soluble form of P selectin glycoprotein ligand 1, tandem P selectin glycoprotein ligand immunoglobulin (TSGL‐Ig), in a mouse model of hepatic cold preservation (4°C in University of Wisconsin solution for 20 h) and syngeneic orthotopic liver transplantation (OLT). Unlike controls, TSGL‐Ig protected orthotopic liver transplants against ischemia–reperfusion (IR) stress, shown by depressed serum alanine aminotransferase levels, well‐preserved hepatic architecture, and improved survival (42% vs. 92%). TSGL‐Ig suppressed neutrophil/macrophage sequestration and proinflammatory cytokine/chemokine programs in OLT. Treatment with TSGL‐Ig mitigated LEC activation (P and E selectin, VCAM‐1 and intercellular adhesion molecule 1 expression). In parallel in vitro studies, TSGL‐Ig diminished cellular damage in H2 O2 ‐stressed LEC cultures (lactic acid dehydrogenase and alanine aminotransferase levels). Increased thioredoxin, glutamate‐cysteine ligase, NAD(P)H quinone dehydrogenase 1, and hypoxia‐inducible factor 1α expression, along with transcription factor nuclear factor erythroid 2–related factor 2 (Nrf2), implied that TSGL‐Ig exerts antioxidant functions in IR‐stressed OLT and H2 O2 ‐stressed LECs. Indeed, Nrf2‐deficient livers suffered fulminant IRI compared with WT despite concomitant TSGL‐Ig therapy. Thus, TSGL‐Ig is not only acting as a competitive antagonist blocking leukocyte migration into IR‐stressed liver, but it may also act directly as an agonist stimulating Nrf2‐mediated cytoprotection in LECs. This study supports the role of P selectin signaling in hepatic homeostasis in OLT, with broad implications for tissue damage conditions. Abstract : TSGL‐Ig protection of liver endothelial cells mediated via antioxidant Nrf2 in hepatic ischemia–reperfusion injury highlights multifaceted functions of P‐selectin signaling beyond cell trafficking, of direct relevance in organ transplantation.